Die Vorrede zur Froschauer Bibel von 1531: Einleitung, annotierte Übersetzung, Transkription - Opitz, Peter (Zwingliana, 2021)
There is no author’s name in the preface to the Froschau Bible of 1531. However, everything indicates that it is from Leo Jud, who drafts it on behalf of a group of translators and editors. The purpose is to motivate and guide broad public readers to read the Bible. The Froschau Bible of 1531 contains, for the first time, not only the New Testament, but also the entire Old Testament and the apocryphal books in German translation. Accordingly, the preface gives a brief introduction to the Old Testament books and the Apocrypha. It is obvious that the Zurich Reformation appreciatively falls back on the works of Erasmus as well as drawing on Augustine. Reformation and humanism are not contradictory in the Zurich Reformation. Rather, humanism is incorporated into the Reformation. This is also the case in the preface to the Froschau Bible. However, a closer look reveals that the references to Erasmus are selective and critical. While Erasmus, influenced by the mystical Theology of Pseudo-Dionysius, sees the Bible as a guide to piety and the promotion of Christian virtues on a spiritual path leading to God, the preface presents the Bible as theocentric: it bears witness to God’s activity and revelation and is the place where God encounters human beings. It is deeply rooted in Zwingli’s theology. While in the Roman Church, the sacraments administered by priests were the place where the encounter with God took place, this now became the reading of the Bible. It was to be read not only in church worship service, but also in families. With the spread of the Bible in vernacular languages, the congregation was made mature and removed from the control of the church hierarchy.